2021
DOI: 10.3390/biomedicines9060681
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Like Effect of Mitotane Explained by Its Agonist Activity on Estrogen Receptor-α

Abstract: Mitotane is the cornerstone of medical treatment of adrenocortical carcinoma. Estrogenic-like side effects frequently occur in patients, and previous studies explored the chemical nature of the interaction between estrogen receptor-α (ER-α) and toxic compounds, including the DDD derivatives. We used molecular docking and molecular dynamics (MD) simulations to explore the possible interaction between mitotane and the ER-α receptor and the induced conformational changes. The ER-α expressing MCF-7 cells were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Studies showed that if a special substance tends to affect Er α and Er β as an agonist or relative agonist it should be placed at the interaction distance of the active site of amino acids Glu353, Arg394, and His524, but for an antagonist, it differs and just one missing interaction can have the opposite effect [ 70 ]. To evaluate the physiological behavior of ligands in the vicinity of enzymes, the binding affinity (binding energy) of ligands to receptors is important (Figures 6 – 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that if a special substance tends to affect Er α and Er β as an agonist or relative agonist it should be placed at the interaction distance of the active site of amino acids Glu353, Arg394, and His524, but for an antagonist, it differs and just one missing interaction can have the opposite effect [ 70 ]. To evaluate the physiological behavior of ligands in the vicinity of enzymes, the binding affinity (binding energy) of ligands to receptors is important (Figures 6 – 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…The research conducted by Rossini et al . demonstrated that mitotane also directly binds ER-α as an agonist and suggested that selective oestrogen receptor modulators (SERM) or selective oestrogen receptor degrader (SERD) could be clinically useful to antagonize the oestrogen-like mitotane-induced effects [ 51 ]. Mitotane also has oestrogenic action, possibly impacting bone age advancement [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, mitotane also affects the peripheral metabolism of steroids, affecting CBG and SHBG, increasing their concentration in the blood, and thereby reducing the level of free hormones [22,41,57]. Additionally, the substance directly binds to the oestrogen receptor (α) as an agonist, causing the oestrogen-like mitotane-induced effects [58].…”
Section: Discussionmentioning
confidence: 99%